The institutional structure of antitrust enforcement - Crane, Daniel A. (New York ; Oxford : Oxford University Press, 2011)
This text provides a comprehensive and succinct treatment of the history, structure, and behaviour of the various US institutions that enforce antitrust laws. It also draws comparisons with the structure of institutional enforcement outside the US, and it considers the possibility of creating international antitrust institutions.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Antitrust law -- United States